What makes mobile apps users loyal? Customer engagement and customer equity roles - Afiff Wira Pradana; Sri Rahayu Hijrah Hati (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Discussions regarding app loyalty will assist the company in developing existing features and creating new features. This study aims to determine customer equity mediation's role in customer engagement and loyalty. This study's novelty discusses factors that determine loyalty. Respondents in this study were the MyPertamina (application for cashless payment at Pertamina's public gas filling stations) users of 218 people registered in Indonesia. This research uses descriptive research design (cross-sectional) and Structural Equation Modeling (SEM). The research data were processed by using SmartPLS software with a partial least square technique to test the hypothesis. The empirical findings show that customer engagement positively affects customer equity, customer equity positively affects customer loyalty, and customer equity mediates the influence between customer engagement and customer loyalty.